The feminine and the masculine in the dream imagery of career-oriented women - a post-Jungian perspective - Griessel, Loura (University of the Free State, 1999)
The central aim of this study is to explore the archetypal Feminine and Masculine in the dream imagery of career-oriented women in order to understand more about their developmental patterns and dynamics, especially within white Afrikaner culture. The study is theoretically grounded in the analytical psychology of C.G. Jung. In evolving his ideas on psychological development, Jung sees development and individuation as embedded in the archetypes of the Feminine (nurturing, interrelatedness, immersion in life, empathy) and the Masculine (autonomous, separateness, aggressiveness). Jung argues that women instinctively have more of these Feminine qualities and live in a Feminine consciousness, while men have more of a Masculine consciousness. Post-Jungians have come to understand that, as a result of gender and cultural conditioning in the western patriarchy, women, as a result of their experiences, tend to have the archetypal Feminine patterns and ways of being mediating themselves. Post-Jungian thinking has led to an understanding that Feminine and Masculine consciousness are open to both sexes from birth. A post-Jungian developmental model regards the Feminine and Masculine as the basic principles in which all other archetypes partake. They are used to explain the developmental patterns of the Self and ego-consciousness over a life-time. Thus this post-Jungian model becomes a way in which to understand the developmental patterns of the Self in career-oriented women by using the Feminine and Masculine principles, their images, and forms. In the Jungian paradigm, the world of industrialised market-related work forms part of the Masculine archetypal principle with its modes of consciousness in its heroic drivenness, aggression, goal-orientation, and regulatory nature. Thus, career-oriented women would tend to move closer to, and even identify with, the world of the Masculine and its modes of consciousness, while leaving more of their Feminine qualities in the unconsciousness. These considerations lead to the questions of what Feminine and Masculine themes emerge in the dream imagery of career-oriented women and how they relate to the developmental model of the Self which explains development in terms of the Feminine-Masculine polarity. This investigation also indicates particular images with which these women are identified and which mediate their ego-consciousness and ways of being. The first part of the literature study deals with Jung's understanding of the dynamics of the psyche and how these pertain to the two basic archetypal principles of the Feminine and Masculine. The focus is on the developmental model of the Self which integrates Jung's work and current post-Jungian thinking. This part also explores the Feminine and Masculine principles, their forms, images and structures. The second part of the literature study focuses on the Masculine nature of work. The last part of the literature study deals with an adapted model of the Self, using the archetypal Feminine and Masculine, for career-oriented women. To address the research questions empirically, a hermeneutically-grounded thematic analysis of 128 dreams reported by career-oriented women of Afrikaner origin was undertaken. Nineteen themes emerged from the data, each of which has been elucidated in turn, using Jung's method of amplification. This process yielded two concise themes, the Feminine and the Masculine. This study concludes that the dream imagery in career-oriented women reveals more Feminine themes (fifteen) than Masculine (nine), indicating that these women have as a group moved closer to the Masculine modes of consciousness with their specific implications for development and individuation. The structural or typological images mediating these modes of consciousness are identified and described within the developmental model of the Self. The clinical implications of these findings and indications for further research are explained.
Thesis (Ph.D. (Industrial Psychology))--University of the Free State, 1999
Keywords: Imagery (Psychology); Women and psychoanalysis; Dreams -- Psychological aspects